Differences in Self-Efficacy, Self-Management, and Achievement Index of Students in the Tadris IPS IAIN Kudus Study Program - Abi Amar Zubair; Yusuf Falaq; Rofiq Faudy Akbar (Universitas Pendidikan Indonesia, 2024)
Gender studies explain the differences in roles, positions, attitudes, behaviour, intelligence, and emotions between men and women. The concepts of study habits, adaptation, and academic assignments trigger differences in batches of students. On the other hand, the double burden students carry apart from academic interests can make students' achievement indexes fail to meet expectations. This triggers differences in intelligence and self-management based on the burden they carry. This research aims to determine whether there are differences in the self-efficacy, self-management, and achievement index of Tadris IPS IAIN Kudus students in terms of gender, batch of students, and student burden status. This research uses a quantitative approach and a survey method. The results show differences in self-efficacy, self-management, and achievement index based on gender. Women are taller than men. A review of the differences among the batch of students shows differences in self-efficacy and achievement index, while there is no difference in self-management. A review of student loads did not show differences in student self-efficacy, self-management, and achievement index. In conclusion, there are differences in gender, self-efficacy and achievement index based on the batch of students, but no differences in student status.